Systems Thinking in a Second Grade Curriculum: Students Engaged to Address a Statewide Drought - Curwen, Margaret Sauceda; Ardell, Amy; MacGillivray, Laurie; Lambert, Rachel (Frontiers in Education, 2018)
Faced with issues such as climate change, educators around the world acknowledge the need for developing students' ability to solve problems within and across contexts. A systems thinking pedagogy, which recognizes the interdependence and interconnected relationships among concrete elements and abstract concepts (Meadows, 2008; Senge et al., 2012), has potential to transform the classroom into a space of observing, theorizing, discovering, and analyzing, thus linking academic learning to the real world. In a qualitative case study in one school located in a major metropolitan area in California, USA teachers and their seven- and eight-year-old students used systems thinking in an interdisciplinary project-based curriculum. Through reflection and investigations, students devised solutions and used innovative approaches to publicly engage peers and family members in taking action to address an environmental crisis.